Effects of NP-SR Fertilizer Composition and Water Logging on Soil Chemical Properties and N Fertilizer Efficiency in Paddy Field - Sari, Tiara Kartika; Rif’an, Muhammad; Sakhidin, Sakhidin (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2021)
Rice is the primary food commodity in Indonesia. To increase the rice production, urea fertilizer has been excessively used, specifically on marginal land. However, it has no desired effect on the plant’s Nitrogen uptake due to volatilization. Previous studies suggest the use of zeolite to be mixed with urea to reduce the volatilization rate. This study aimed to determine the effect of six NP-SR (Nitrogen Phosphorus Slow Release) fertilizer compositions (without NP-SR; 20.69-0; 19.7-5; 17.27-10; 15.9-15; and 18.94-20) on soil chemical properties, nitrogen efficiency, and paddy rice yield on Ultisols at three waterlogging levels (0.5 cm, 3 cm, and 5 cm). The study was an experiment arranged in a Randomized Complete Block Design (RCBD) consisting of two factors, which were waterlogging levels and NP-SR fertilizer compositions. The results showed that waterlogging treatments significantly affected soil chemical properties in the initial vegetative and harvest phases. It can be concluded that the treatment of flooding (up to 3 cm) and fertilizer (NP-SR of 15.90-15) application could significantly reduce the volatilization rate, increase the efficiency of N fertilizer, and increase rice yield.